(untitled) (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This research is titled "Japanese Wakamono Kotoba Translation Procedures in Indonesian Subtitle Caption on VSI YouTube Channel." Wakamono kotoba or Japanese slang, is widely used as a young people’s language, particularly by VTubers, and is frequently translated by fan-translation channels such as VSI (VTuber Sub Indo). This study aims to identify the characteristics of wakamono kotoba, analyze the translation procedures used in translating them into Indonesian subtitles, and examine the equivalence of the translations. The data in this research consist of wakamono kotoba utterances and their translations sourced from Hololive VTuber videos on the VSI YouTube channel between 2023 and 2024. This research employs a qualitative approach as described by Creswell, with an observation method for data collection and a comparison technique as used by Maxwell for data analysis. The theories applied in this research include wakamono kotoba characteristics by Tanaka, translation procedures by Vinay and Darbelnet, and translation equivalence by Nida and Taber. The results show that almost all characteristics of wakamono kotoba were found, except for the reversing of word structure (Sakasa Kotoba), with word shortening (Shouryaku) being the most frequently found. The equivalence procedure was the most widely used, while calque and literal translation were not found. Both formal and dynamic equivalence were able to convey the intended meaning in the Indonesian subtitles